Green manuring of beans intercropped with coffee in family farming of Araponga, Minas Gerais, Brazil - Sousa, Filipe Fernandes de; Santos, Ricardo Henrique Silva; Carneiro, José Eustáquio de Souza; Urquiaga, Segundo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Bean intercropping cultivation is common practice among farmers in the Zona da Mata, Minas Gerais, which promote the diversification production of their areas aiming mainly the production of food for family consumption. Diagnostics of university extension projects identified family farmers who beside the consortium with coffee trees, use legumes in pre-cultivation to beans for green manure, increasing biological process that contribute to the complexity an sustainability agroecosystems. Thus, the objective of this work was to evaluate species of leguminous plants in pre cultivation and the influence on the bean in consortium system with coffee under the management in the family farmer. The evaluation was conducted in rural property and jointly with the farmer. The evaluated legumes were the jack bean and the hyacinth bean, besides a witness represented by the spontaneous vegetation. A randomized block design with eight replications was adopted, with each interlayer of coffee trees representing one block. The variables analyzed were: fresh and dry matter productivity; content and accumulation of N; contribution of BNF in preculture; and productivity of beans grown in succession. The jack bean was the legumes that presented the largest production of fresh and dry matter (19.04 and 4.25 t ha-1, respectively), accumulated more N (113.99 kg ha-1) and contributed the largest amount of N-system FBN (49.18 kg ha-1). However, pre-cultivation with legumes did not influence the productivity of the bean grown in succession.